Inpatient and outpatient nephrology management of critically ill patients with acute kidney injury. Issue 4 (10th December 2020) - Ransley, David G.; See, Emily J.; Mizrahi, Alice; Robbins, Ray; Bellomo, Rinaldo
Abstract: Introduction: Acute kidney injury (AKI) during critical illness increases the risk of subsequent chronic kidney disease. Guidelines recommend inpatient nephrology assessment and review at 3 months. Objectives: To quantify the prevalence and predictors of inpatient and outpatient nephrology follow‐up of AKI patients admitted to critical care areas within a tertiary hospital. Methods: Retrospective study of all critically ill adults with AKI between January 1, 2012 and December 31, 2016 with a baseline estimated glomerular filtration rate (eGFR) >30 mL/min/1.73 m 2 and alive and independent of renal replacement therapy for 30 days after hospital discharge. We used logistic regression models to examine the primary outcome of nephrology review at 3 months. Secondary outcomes included inpatient nephrology review, renal recovery at discharge and the development of a major adverse kidney event (MAKE) at 1 year. Results: Of 702 critically ill patients with AKI (mean age 66 years, 64% male, baseline eGFR 78 mL/min/1.73 m 2 ), 43 patients (6%) received nephrology follow‐up at 3 months and 63 patients (9%) at 1 year. Nephrology follow‐up occurred more frequently in patients with a higher baseline creatinine, a higher discharge creatinine and greater severity of AKI. Seventy patients (10%) underwent inpatient nephrology review. Overall, 414 (59%) had recovery of renal function by the time of discharge and 239 (34%) developed a MAKE at 12 months. Conclusion: Inpatient and outpatient nephrology follow‐up of AKI patients after admission to a critical care area was uncommon although one‐third developed a MAKE. These findings provide the rationale for controlled studies of nephrology follow‐up. SUMMARY AT A GLANCE: This article provided new insights for post‐acute kidney injury (AKI) care after discharge from the intensive care units. Less than 10% of patients have been followed up while nearly 35% developed a major adverse kidney event (MAKE) at 1 year, calling for attention in providing nephrology follow‐up after AKI.